RADICAL DEMOCRACY'S PAST AND FUTURE: HISTORIES OF THE SYMBOLIC*. (16th June 2015) - WEYMANS, WIM
Abstract : A few decades after the linguistic turn began affecting them, historians are now writing its history. For one of them the linguistic turn meant much more than just an acknowledgement of the importance of language and signs. In his latest book, appropriately called Adventures of the Symbolic, Warren Breckman argues instead that the linguistic turn was part of a much broader "symbolic turn" (266). His book is a rich collection of previously published articles that all deal with "the symbolic" in different times (from the eighteenth century till today) and places (mainly France and Germany and to a lesser extent the UK). That survey begins with the Romantics, whose focus on the symbolic dimension was criticized by Hegel and Marx, but praised by Leroux. The concept resurfaced in France, first with Durkheim and Mauss and later with Lévi-Strauss, Merleau-Ponty and Lacan, who in turn influenced Castoriadis and Lefort. These last three thinkers all had a significant impact on the following generation represented by Gauchet, Laclau, Mouffe and Žižek, to whom Breckman devotes the second half of his book. One merit of his book is that Breckman analyzes and presents figures like Leroux, Castoriadis, Lefort, Gauchet and Laclau who are important for political theory and intellectual history, yet remain under-researched and relatively unknown.